ANALISIS TINGKAT PENDAPATAN USAHATANI ALPUKAT DI KELOMPOK TANI KABUPATEN SEMARANG - Dytanti Ilmiansi Tamalia; Siswanto Imam Santoso; Kustopo Budihajo (MEDIAGRO, 2018)
The purpose of this research is to know the level of avocado farm income and to know the influence of production quantity, labor cost, fertilizer cost, and selling price of avocado to farmer's income in Bandungan and Sumowono District, Semarang Regency. The study was conducted from January to March 2017 in Bandungan and Sumowono Districts. The method used in this research is survey method. The method used in determining the location of the research is purposive and the sampling method using random sampling method, and the number of respondents is determined by quota of 20 farmers in Bandungan and 20 farmers in Sumowono District. The analysis used is income analysis, profitability, one sample t-test, and multiple linear regression analysis. The results showed that the average income of farmers per year amounted to Rp 32,881,705.00, the average of profitability is 7.72%, and one sample t-test showed that the significance level is 0.044, so it can be concluded that avocado farming that is done by farmers is generate profitable income, while the result of production factors that positively affect the net income of avocado farmers is the amount of production, labor cost, and selling price of avocado. The fertilizer cost factor does not positively affect the net income of avocado farmers.Keywords: Income, Profitability, Production quantity, Production cost, Avocado.